Balancing Family Unity Principle and Familial Ties Prohibitions in Banyumas Credit Union Management - Maria Mu'ti Wulandari (Notaire, 2025)
The framework of Credit Unions (KSP) in Indonesia emphasizes family unity, grounded in Pancasila and the 1945 Constitution. The 2023 Ministry regulation restriction on familial ties in KSP management roles, prompting a study of balancing family unity with these prohibitions. This research sought to explore the balance between the family unity principle and the restrictions on familial ties in KSP management. This research adopted a sociological juridical approach, with data collection conducted through observation, in-depth interviews, and the acquisition of official documents from the Banyumas District Department of Labor, Cooperatives, and SMEs. The gathered data were subsequently analyzed using an analytical descriptive method. The findings revealed that out of the 54 KSPs operating from 2019 to 2023 in Banyumas, 10 were classified as Healthy, 43 as Moderately Healthy, and one Under Supervision. A balance between the two examined aspects was observed in the practices of various KSPs in Banyumas, though there remains room for strengthening the application of the family unity principle. In conclusion, within the context of “Balancing Family Unity Principle and Familial Ties Prohibitions in Banyumas Credit Union Management,” it is evident that KSPs in Banyumas have implemented the family unity principle while considering the prohibition of familial ties to prevent conflicts of interest, thereby enhancing the welfare and sustainability of the KSPs. Given these findings, it is recommended that structured education and training on harmonizing these principles be introduced to further enhance the health and functioning of KSPs in Banyumas.